Desain dan Implementasi Alat Pengisi Bahan Bakar Otomatis Pada Kapal Kayu 6 GT - Harahap, Basyaruddin Ismail; Sandi, Kurnia; Kusuma, Hollanda Arief; Yunianto, Anton Hekso (Newton-Maxwell Journal of Physics, 2025)
To reduce pollution caused by fuel spills during the refueling process, this research designs and implements an automatic fuel filling device on a wooden boat with a capacity of 6 GT. This system consists of the JSN-SR04T ultrasonic sensor unit, an automatic pump, Neopixel-based LED visual indicators, and a microcontroller as the control center. This tool is designed to automate the fuel transfer process from the dock tank to the ship's tank without the need for manual intervention, thereby increasing operational efficiency and safety. Laboratory tests show that the system has high accuracy, with a Root Mean Square Error (RMSE) value of 0.30 cm, equivalent to an accuracy level of 99.39% in measuring the fuel surface height. In field tests on the Sungai Ungar–Batam route, this device was able to fill 75.76 liters of fuel in 9 minutes and 29.15 liters in 3 minutes automatically. The system is capable of detecting fuel levels, activating the pump when needed, and providing real-time visual notifications. The system's performance is affected by turbulence in the tank when the ship is moving, which reduces the stability of the sensor readings. Therefore, the use of sensors that are more resistant to dynamic conditions and the expansion of testing on larger capacity ships will be the next direction for development.